A scoping analysis of the counter terrorism command policing structure and its impact on intelligence sharing between the police and the security services. Issue 3 (3rd July 2023) - Halford, Eric
ABSTRACT: Counter-terrorism (CT) policing in the United Kingdom is presently delivered by Counter Terrorism Policing Headquarters (CTPHQ) through their Counter Terrorism Command (CTC) in the Metropolitan police. Their work is supported by 11 regional police counter-terrorism units (CTUs) across the UK. This is a relatively new model and as a result, joint working with the UK security Services (MI5) has significantly changed. With increased focus on collaboratively gathering and sharing CT intelligence the new structure and working relationships were designed to overcome existing impediments to intelligence sharing to improve the UKs CT capability. Since the changes, there has been limited empirical assessment of their impact. To address this, our preliminary study uses a mixture of questionnaires and interviews with CT officers in a single CTU to analyze the blockers and enablers of intelligence sharing since the shift to this new working model. Results indicate significant improvements in bilateral intelligence sharing between the police and security services. Responses suggest this has primarily been driven by closer joint working that has enabled higher frequency face-to-face contact. We discuss the findings in the context of implications for the UK's ability to combat terrorism and future ways to continue improvements.